Anaerobic treatment using two-phase downflow stationary fixed-film reactor - Ying, Wong Ching; Hanaki, K.; Samorn Muttamara; Vigneswaran, Saravanamuthu; DAAD, Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1987)
The application of DSFF reactor to both two phase and single phase anaerobic system was studied. The performance of DSFF reactors in methanogenic phase, which received the different organic acid as carbon and energy source, was also investigated. The effect of phase seperation over single phase system and the effect of different organic acid over methanogenic efficiency was evaluated. One mixed flow reactor was used as acidogenic reactor for two phase system and all reactors were operated in 35 degree C temperature controlled room. Same concentration (5000 mg/l) of glucose or acetic acid was used in each system in order to make direct comparison. It was found that DSFF reactor can be applied to both single phase and two phase system with acceptable process performance. DSFF reactors were very stable and tolerant to operational accident. Two phase system has no significant advantage over single phase system in this study. The methane fermentation by acetate alone failed to maintain methanogenic enrichment whereas the bacteria receiving the various organic acid other than acetic acid could perform well. Type of material and architecture of supporting media are very important functions for application of DSFF reactor in anaerobic digestion process. The packing material made with acrylic corrugated plastic sheet could not provide the good biofilm attachment resulting in less process performance than that of maximum obtainable one .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Sewage -- Purification -- Biological treatment